IDENTIFIKASI BAKTERI FLORA NORMAL MUKOSA HIDUNG DAN SALIVA PADA PENAMBANG EMAS (TROMOL) DI KELURAHAN POBOYA KECAMATAN PALU TIMUR SULAWESI TENGAH - Yuni Tiara; Muhammad Alwi; Musjaya M. Guli (Biocelebes, 2014)
Research on the “Identification Of Normal Bacterial Flora of Nasal Mucosa and Salivary Gold (Tromol) Mining Village In The District Poboya Palu Central Sulawesi East” have been performed. Purpose of this study was to determine the type of bacterial that are normal flora in nasal mucosa and salivary poboya gold miners and todetermine the percentage of normal flora laboratory. Research method that was done in two stages field sampling and laboratory axamination. Sampling done by random. As for the number of samples that 30 consisting of 15 saliva and nasal mucosa 15. Result obtaind in the nasal mucosa was Enterobacter aerogenosa the proportion 18.1%, Staphyllococus aureus the proportion 36.4%, Proteus mirabilis the proportion 9.1%, Escherichia coli the proportion 9.1%, Enterobacter agglomerans the proportion 27.3%. Keywords : Identification, Normal Bacterial Flora, Nasal Mucosa, Salivary.